Roosting behaviour of greater noctule bats (Nyctalus lasiopterus) in forests in Spain and implications for species conservation and forest management - Detlev H. Kelm; David Pastor-Bevia; Jesús Nogueras; Ana G. Popa-Lisseanu; Íñigo Sánchez; Carlos Ibáñez (Royal Society Open Science)
The greater noctule (Nyctalus lasiopterus) is a threatened tree-roosting bat species with a fragmented distribution, possibly due to limited roosting habitat. Deforestation, tree disease and climate change are reducing forest and roost availability. Effective conservation action and forest management require detailed knowledge of the bats’ roosting behaviour and requirements, which is lacking for this species, particularly in southern European forests. We studied the roosting behaviour of 25 radio-tagged females from three maternity colonies in the forest and the urban environment, as well as 11 males from a forest mating site in Spain. We found similar behaviour and roost group sizes (14–18 individuals) for both sexes in the forest, where bats mainly roosted in woodpecker holes in larger trees of abundant tree species. Bats switched between many roosts (0.2–0.3 roosts d−1) across large forest areas (up to 1300 ha). At the urban site, females rarely switched between four exotic palm tree roosts, with roost group sizes reaching 144 individuals. Despite its adaptability, N. lasiopterus may require large forest roosting areas that provide a greater roost diversity, aiding thermoregulation and predator avoidance. Conservation efforts should focus on protecting large forests with high woodpecker abundance to ensure roost availability, supported by artificial bat roosts.